Energy-efficient ethanol recovery process using 2-methyl pentanol extraction. (15th February 2022) - Lee, Seong Chan; Woo, Hee Chul; Kim, Young Han
Highlights: 97% of water in feedstock is removed during extraction with no energy demand. 2-Methyl pentanol is proposed as a new extraction solvent. Molecular simulations and experiments were conducted for thermodynamic modeling. The energy demand is reduced by 31% when compared to the current processes. Abstract: Bioethanol is commonly recovered via distillation due to the availability of abundant biowaste as an energy source. Although extraction is a well-known energy-efficient process that can replace distillation, appropriate solvents have not been developed for ethanol recovery. Herein, a branched long-chain alcohol, 2-methyl pentanol, has been proposed as an extraction solvent. Thermodynamic models of vapor–liquid equilibrium (VLE) and liquid–liquid equilibrium (LLE) systems have been constructed using molecular simulations and experimental results for the development of the extraction process and ethanol concentration using ethylene–glycol extractive distillation. The optimized process design demonstrates that the heat duty can be reduced by nearly a third compared to that obtained using the previous recovery processes.